2018
DOI: 10.1021/acs.jctc.8b00406
|View full text |Cite
|
Sign up to set email alerts
|

A Mountaineering Strategy to Excited States: Highly Accurate Reference Energies and Benchmarks

Abstract: Striving to define very accurate vertical transition energies, we perform both high-level coupled cluster (CC) calculations (up to CCSDTQP) and selected configuration interaction (sCI) calculations (up to several millions of determinants) for 18 small compounds (water, hydrogen sulfide, ammonia, hydrogen chloride, dinitrogen, carbon monoxide, acetylene, ethylene, formaldehyde, methanimine, thioformaldehyde, acetaldehyde, cyclopropene, diazomethane, formamide, ketene, nitrosomethane, and the smallest streptocya… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

104
667
6
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 309 publications
(783 citation statements)
references
References 276 publications
(731 reference statements)
104
667
6
6
Order By: Relevance
“…In terms of absorption energies, the calculations overestimate experiment by about 0.5 eV with 6-31 + G(d,p), and 0.3-0.4 eV with aug-cc-pVDZ, see Table 1, which is typical for this level of theory/basis set combination. [9] The emission energy for the LE state is overestimated by 0.4 eV with the small basis set, and 0.3 eV for the larger one, see Table 2. The comparison with an extrapolated value of the experimental CT emission energy shows that the calculations underestimate this quantity by 0.4-0.46 eV; this underestimation is discussed in more detail later, when we present the data in acetonitrile.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In terms of absorption energies, the calculations overestimate experiment by about 0.5 eV with 6-31 + G(d,p), and 0.3-0.4 eV with aug-cc-pVDZ, see Table 1, which is typical for this level of theory/basis set combination. [9] The emission energy for the LE state is overestimated by 0.4 eV with the small basis set, and 0.3 eV for the larger one, see Table 2. The comparison with an extrapolated value of the experimental CT emission energy shows that the calculations underestimate this quantity by 0.4-0.46 eV; this underestimation is discussed in more detail later, when we present the data in acetonitrile.…”
Section: Resultsmentioning
confidence: 93%
“…Although implicit models represent a drastic approximation in the description of the environment, it is still important to treat the solute with a high level of theory, because the accurate description of the solute electron density is ultimately responsible for the reliability of the simulation. [9] In previous work, we presented the theory and implementation of excited state energy and energy gradients with the equation of motion single and double excitations method (EOM-CCSD), [10] combined with PCM within the state specific (SS) solvation formalism. [11,12] This approach describes the solvent polarization response to the excited state solute electron density, thus the solute-solvent interaction in the excited state is treated more completely.…”
Section: Introductionmentioning
confidence: 99%
“…For the vertical singlet excitation, there is also a recent 4.06 eV CCSD//CAM-B3LYP estimate, 116 which slightly overshoots ours, consistent with the expected error sign of CCSD. 20,70,117 Silylidene. One notes an excellent agreement between CCSDT, CCSDTQ, and FCI for this derivative.…”
Section: Results and Discussion 31 Exotic Set 311 Reference Valuesmentioning
confidence: 99%
“…Our computational protocol closely follows the one of Ref. 20. Consequently, we only report key elements below.…”
Section: Methodsmentioning
confidence: 99%
“…[31] Although CC2 performed best for singlet excitation energies, [26,31] CCSD performed slightly better for triplet excitation energies. [31] In a recent study by Loos et al [34] on 106 different singlet and triplet excited states, the CCSD method was found to perform slightly better than CC2 and again the CC3 method was found to perform very well-giving results almost identical to the CCSDT and coupled cluster singles, doubles, triples and quadruples (CCSDTQ) methods. In this study, we have chosen to use the CC3 results as reference values.…”
Section: Introductionmentioning
confidence: 99%